PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT VOLEX DI BATAM - Wahid, Sopian; Nainggolan, Nora Pitri (LPPM Universitas Putera Batam, 2022)
The purpose of this study is to analyze the effect of work discipline and work environment individually (partially) or simultaneously (simultaneously) on employee performance at PT Volex in Batam. The sampling technique used in this research is purposive sampling. The population in this study are employees who work at PT Volex in Batam with a total population of 520 employees. By raising as many as 226 respondents as a sample. And using the help of SPSS 26 software to calculate the test results. The results of this study prove that partially work discipline and work environment have a significant influence on employee performance at PT Volex in Batam, with a t value of work discipline (X1) 8.116 > t table 1.651 and work environment (X2) 9.515 > t table 1,651. The results of this study also prove that simultaneously (simultaneous) work discipline and work environment have a significant influence on employee performance at PT Volex in Batam.